Knowledge, attitudes and practices of heads of households on malaria in rural Phalombe - Yakobe, Yankho (Kamuzu University of Health Sciences, 2022)
This descriptive quantitative study was conducted in order to find out the depth of knowledge, attitudes and practices of heads of households in rural Phalombe. It was done in Traditional Authority (TA) Mkhumba. The sample comprised of 30 subjects from 5 villages, 6 subjects from each village using convenient sampling. A structured interview guide was used to collect the data and the data was analysed manually. The results indicated that the majority of the participants had knowledge on mode of transmission, signs and symptoms, treatment, prevention and complications of malaria. The majority 83.3% of the participants sleep under a mosquito net in order to protect themselves from malaria. However most of the mosquito nets were not treated in time. The results also show that the majority lacked knowledge on the dosages for particular age groups. Some participants 43.3% mentioned the burning of smelly staff such as dung's of goat, rubber, cedar and blue gum as a means of chasing and killing mosquitoes which can be detrimental to health.